Practicing Fashion with the Anthropocene - Patricia Wu Wu (Temes de Disseny)
Odradek, a strange creature in Franz Kafka’s tale “The Cares of a Family Man,” outlives the narrator, thus becoming a device to think about a world devoid of any narrative necessity. In the story, Odradek sends semiotic ripples into the vectors of a future, where its reverberations spread into an ontologically withdrawn world, inaccessible to human thought. Odradek is a symbol, a strange totem of the agitation caused by the thought of human extinction as it embodies the fear of being outlived by a non-human entity. The semiotic relationship of Odradek with the narrator is synonymous to our relationship with the Anthropocene — the geological epoch in which human-induced activities have drastically altered the Earth (Crutzen et al. 2011). At the very core of the Anthropocene is a glimpse of a future in which the human subject, similar to the narrator, cedes its sovereign executive functions in the face of an abstract reality.